Actitudes hacia la conservación del ambiente en alumnos de secundaria de una institución educativa de Ventanilla - Chalco Ramos, Lourdes Nancy (2012)
The work aimed to describe the attitudes towards environmental conservation of secondary school students of an educational institution in the district of Callao window. The sample belonged 150 pupils males and women of 1er to 5to year of secondary, with ages between 11 and 16 years. We used the scale of attitudes toward environmental conservation (Yarlequé Chocas, 2004). This corresponds to a descriptive research. The results indicate that most students have a low attitude towards environmental conservation, in terms of the components: cognitive, affective and reactive, most students of secondary level of IE Ventanilla have low attitude towards environmental conservation. The same results yielded by age group.